From hijṛā to kinnara: autobiographical narratives mirroring contradictory drives (Altre Modernità, 2024)
In this contribution, we would like to reflect on some aspects and dynamics that characterise hijṛā activism in contemporary India, focusing first on the role of narrative and autobiographical production as a vehicle of knowledge and disclosure of the existential conditions of the hijṛā community. In addition to providing generally accurate descriptions of the socio-cultural peculiarities of the hijṛā universe and raising the reader's awareness of the conditions within which the existence of its members unfolds, narratives connect global socio-political recognition instances with urges and impulses from local culture. The 'glocalised' hijṛā activism on the one hand flows into and participates in a broader movement of rights claims while, on the other hand, interacting with the specificities of the Indian social fabric. The creative and practical effort against the drive for normalisation implicit in hijṛā activism thus gives way to the urgency of a socio-legal recognition of hijra otherness, achieved through the application of a homo-hetero binary structure to a heterogeneous, multifaceted universe of practices and memberships that is irreducible to a univocal identity construction. We will therefore analyse the logic behind the socio-cultural recognition demanded by hijṛā activists and, in particular, by Laxmi Narayan Tripathi who, by replacing the appellation hijṛā with the term kinnara, evocative of the Brahmanical cultural heritage, confers, according to the well-trodden dynamics underlying the creation of essentialist identities, socio-cultural legitimacy and political expendability to hijṛā liminality.
Keywords: hijṛā; third gender; eunuchs; kinnara; autobiographies